2005
DOI: 10.1016/j.jimonfin.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pricing default swaps: Empirical evidence

Abstract: In this paper we compare market prices of credit default swaps with model prices. We show that a simple reduced form model outperforms directly comparing bonds' credit spreads to default swap premiums. We find that the model yields unbiased premium estimates for default swaps on investment grade issuers, but only if we use swap or repo rates as proxy for default-free interest rates. This indicates that the government curve is no longer seen as the reference default-free curve. We also show that the model is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
108
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(119 citation statements)
references
References 37 publications
11
108
0
Order By: Relevance
“…Namely, both in academic studies and industry reports it has been common practice to fix corporate LGD at its historical average of 60% (cf. Houweling and Vorst (2005), Chen, Cheng, and Wu (2005), Longstaff, Mithal, and Neis (2005), Chen, Cheng, Cao, and Chen (1997) criterion our estimated risk premia imply reasonable risk preferences.…”
Section: Introductionmentioning
confidence: 66%
“…Namely, both in academic studies and industry reports it has been common practice to fix corporate LGD at its historical average of 60% (cf. Houweling and Vorst (2005), Chen, Cheng, and Wu (2005), Longstaff, Mithal, and Neis (2005), Chen, Cheng, Cao, and Chen (1997) criterion our estimated risk premia imply reasonable risk preferences.…”
Section: Introductionmentioning
confidence: 66%
“…Historically, researchers often use Treasury yields to define the instantaneous interest rate and the benchmark yield curve. Houweling and Vorst (2003) perform daily calibration of reduced-form models using credit default swap spreads and find that eurodollar swap rates are better suited than the Treasury yields in defining the benchmark yield curve. Here, we define the benchmark instantaneous interest rate based on the eurodollar libor and swap rates.…”
Section: A Dynamic Term Structure Model Of Interest Rate Default Anmentioning
confidence: 99%
“…The second method is to a priori fix a value. A number of researchers in the economic literature suggest that although the first method seems preferable, it turns out that it is hard to identify the recovery rate from the data, see Duffee (1999), Duffie and Singleton (1999) and Houweling and Vorst (2005). This may pose a problem for some applications; fortunately this does not affect the pricing of credit default swaps.…”
Section: B: Recovery Rate Estimatesmentioning
confidence: 99%
“…This may pose a problem for some applications; fortunately this does not affect the pricing of credit default swaps. Houweling and Vorst (2005) found that the pricing of default swap premium is relatively insensitive to the assumed recovery rate. As such this study assumes a constant recovery rate across the observation period.…”
Section: B: Recovery Rate Estimatesmentioning
confidence: 99%
See 1 more Smart Citation